A PLZT Novel Sensor with Pt Implanted for Biomedical Application: Cardiac Micropulses Detection on Human Skin - Carlos O. González-Morán; José G. Miranda-Hernández; José de Jesús Agustín Flores Cuautle; Ernesto Suaste-Gómez; Héctor Herrera-Hernández (Advances in Materials Science and Engineering)
Advances in sensors for biomedical applications have been a great motivation. In this research, a PLZT (lead lanthanum zirconate titanate) novel sensor with platinum wire implanted in its longitudinal section was developed through of the synthesis process based on powder technology. The raw materials as lead (PbO), lanthanum (La2O3), zircon (ZrO2), and titanium (TiO2) were used in the formation of the chemical composition (62.8% PbO, 4.5% La2O3, 24.2% ZrO2, and 8.5% TiO2). Then, these powders were submitted to mix-mechanical milling at high energy; cylindrical samples with the implant of the platinum wire were obtained with the load application. Finally, the compacted samples were sintered at 1200°C for 2 hours, then followed by a polarization potential of 1500 V/mm at 60°C to obtain a novel sensor. The density and porosity were evaluated using the Archimedes’ principle, while the mechanical properties such as fracture toughness value and Young’s modulus were determined by indentation and ultrasonic methods, respectively. A microscopic examination was also carried out to investigate the structural properties of the material. The PLZT novel sensor is electronically arranged for monitoring the cardiac pulses through a data acquisition system. The results obtained in this research are analyzed and discussed.